2017
DOI: 10.1038/s41598-017-03814-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-leukemia activity of a Hsp70 inhibitor and its hybrid molecules

Abstract: In this study we examined the anti-leukemia activity of a small molecule inhibitor of Hsp70 proteins, apoptozole (Az), and hybrids in which it is linked to an inhibitor of either Hsp90 (geldanamycin) or Abl kinase (imatinib). The results of NMR studies revealed that Az associates with an ATPase domain of Hsc70 and thus blocks ATP binding to the protein. Observations made in the cell study indicated that Az treatment promotes leukemia cell death by activating caspase-dependent apoptosis without affecting the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Thus, it would be more appropriate to describe the transition as a superconductor-metal-insulator transition. The similar intervening metallic phase with substantial superconducting fluctuations was also observed in Ta [7] and MoGe [10], but not in TiN [6], which may be related to the different disorder strengths [20,32].…”
Section: Methodsmentioning
confidence: 63%
See 2 more Smart Citations
“…Thus, it would be more appropriate to describe the transition as a superconductor-metal-insulator transition. The similar intervening metallic phase with substantial superconducting fluctuations was also observed in Ta [7] and MoGe [10], but not in TiN [6], which may be related to the different disorder strengths [20,32].…”
Section: Methodsmentioning
confidence: 63%
“…Superconductor-insulator transition (SIT) as one fascinating example of quantum phase transitions [1] has remained an active topic in recent years. The SIT could be controlled by various non-thermal tuning parameters [2], including disorder [3][4][5][6], thickness [7][8][9], magnetic field [4,7,10,11], chemical composition [12,13], carrier density [4,14], and gate voltage [15,16] in two dimensional (2D) superconductors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, all the binder compounds Gilvocarcin V, Apoptozole, MKT077 and VER-155008 have been reported to directly interact with GRP78 or other Hsp70 family member. Gilvocarcin V mechanism of action was associated with GRP78 by cross-linking 26 , and Apoptozole 29 , MKT-077 27 and VER-155008 30 have been previously characterized for binding to recombinant GRP78. As expected, all these four compounds also engaged the Plasmodium chaperone in our two binding assays.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptozole is an imidazole‐based small molecule that promotes apoptosis in cancer cells through targeting of Hsp70 and Hsc70. It associates with ATPase domain of these molecules and thus blocks ATP binding to the protein . In addition, it has been shown that apoptozole enhances the immune response and antibody production against protein antigens, thus could be used as an adjuvant to increase the efficacy of vaccinated antigens .…”
Section: Hsp70 and Crcmentioning
confidence: 99%